Microplastics in the Mottled Rabbitfish (Siganus fuscescens) in Negros Oriental, Philippines with Notes on the Siganid Fishery - Alcala, Angel C.; Bucol, Abner A.; Bucol, Lilibeth A.; Romano, Edwin F; Cabcaban, Sherlyn; Alvarez, Giselle Ann A.; Ruben, Zoe; Bachner, Micah; Bird, Chris; Polidoro, Beth A.; et al. (Silliman Journal, 2022)
We reviewed the status of the Mottled Rabbitfish (Siganus fuscescens Houttuyn, 1782) as a major fishery product in Negros Oriental, including threats from microplastic pollution and overfishing. This species is often marketed as either fresh or dried “danggit”. Out of a total of 300 fish samples from four areas in Negros Oriental province, 91 (30%) of S. fuscescens ingested microplastics; the highest ingestion (39%) was observed in Dumaguete, a densely populated city. We also assessed the reproductive biology parameters of this species and compared them with the data gathered in 1979, roughly 40 years ago. The samples from Bais and Dumaguete had reduced sizes at sexual maturity and fecundity, suggesting negative effects from prolonged overexploitation. We therefore urge more studies on other parts of Negros Island and even elsewhere in the country, to determine the potential health hazards from microplastic pollution and the current threat to the sustainability of the siganid or “danggit” fishery.